RETRACTED: Analysis of fuel energy efficiency for motor transport in Kazakhstan - Mukhamadeyeva Railya; Orazov Ondassyn; Kassymzhanova Kuralay; Meirkhanuly Seilkhan Omirzhan; Kaliev Bakhyt (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001